7 - Book Reviews: Dr. Jeff Crisp — The Story of an African Working Class: Ghanaian Miners' Struggles 1870—1980. (ZED Press, 57 Caledonian Road — London (1984) - Wilbert B. L. KAPINGA, (Africa Development, 1986)
abstract